1972
DOI: 10.1021/ja00764a008
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of cyclobutane

Abstract: The pyrolysis of cyclobutane has been studied by the VLPP technique between 969 and 1280 K. It was found that the Arrhenius parameters which give best agreement between the present results and those of previous workers are log {k~,, sec-1) = 16.5 -65.5/9. Estimates consistent with the above parameters have been made of the Arrhenius parameters for reactions 2, -2, and 3, c-C4H8 ;=± C4H8• -* 2CZH4 (2, forward; -2, reverse). Studies on the pressure dependence of the rate constant in the 22,400-collision reactor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Beadle et al [19] experimentally studied the pyrolysis of cyclobutane and reported rate parameters for the ring opening of c-C 4 H 8 (k 1-2 and k 2-1 ) and for the decomposition of the biradical in C 2 H 4 (k 2-C2H4 ).…”
Section: Cyclobutanementioning
confidence: 99%
See 2 more Smart Citations
“…Beadle et al [19] experimentally studied the pyrolysis of cyclobutane and reported rate parameters for the ring opening of c-C 4 H 8 (k 1-2 and k 2-1 ) and for the decomposition of the biradical in C 2 H 4 (k 2-C2H4 ).…”
Section: Cyclobutanementioning
confidence: 99%
“…At a given temperature, the global rate constant can be calculated from rate constants given by equations (18) and (19) and equilibrium constant in order to have the ratio of boat and chair conformations. Thus, we obtained the following expression for the global rate constant: …”
Section: Cyclohexanementioning
confidence: 99%
See 1 more Smart Citation
“…The changes in molecular frequencies were estimated by the methods of Benson [2] and by analogy with the transition-state complexes for cyclobutane [20] and isopropenylcyclobutane [ 11. The breaking C-C bond in the biradical transition state was lengthened by 1 A,…”
Section: Cyclobutyl Cyanidementioning
confidence: 99%
“…Experimental data on systems of this type will enable us to exploit our new computational techniques (21. For these studies we use the experimental technique of very low-pressure pyrolysis (VLPP) [4] at pressures such that gas-gas collisions compete with gas-wall collisions [5). As a prelude to energy transfer experiments we have studied the decomposition of CBCL under standard VLPP conditions (that is, where collisional activation is almost entirely via gas-wall collisions) in order to provide confirmation of the unimolecularity of the reactions and as a check on whether the behavior of the reactions in the falloff region is consistent with the high-pressure Arrhenius parameters found by CF.…”
Section: King Caynor and Gilrehtmentioning
confidence: 99%